How Underlying Dimensions of Political Risk Affect Excess Return in Emerging and Developed Markets. (April 2019) - Nesset, Ida Q.; Bøgeberg, Ingrid; Kjærland, Frode; Molden, Lars H.
Political risk is expected to increase due to emerging markets' increasing influence on the world economy. We identify legal, tension, conflict and policy as underlying dimensions through principal component analysis by using a disaggregated political risk index. Using a two-way error correction model, ethnic and religious tension is identified as a new and distinct dimension of political risk. Consequently, global investors are likely to benefit from understanding which dimension implies a reward. Investors in particular should direct their attention towards tension, which seems to command a risk premium regardless of both market and time. JEL Classification: C33, F30, F50, G15